2004
DOI: 10.1111/j.0021-8901.2004.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative approach to conservation planning: using resource selection functions to map the distribution of mountain caribou at multiple spatial scales

Abstract: Summary 1.Visualizing the distribution of rare or threatened species is necessary for effective implementation of conservation initiatives. Generalized linear models and geographical information systems (GIS) are now powerful tools for conservation planning, but issues of data availability, scale and model extrapolation complicate some applications. 2. Mountain caribou are an endangered ecotype of woodland caribou Rangifer tarandus caribou that occurs across central and southern British Columbia, Canada. Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
287
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(295 citation statements)
references
References 56 publications
2
287
0
1
Order By: Relevance
“…Looking across the northern landscape, caribou ecotype and disturbance (e.g., wildfire and/or industrial development) are also likely to be important factors in determining distribution (Mallory & Hillis, 1998;Johnson et al, 2005;Joly et al, 2007a). The importance of each factor is likely to depend on the scale of the analysis (Wiens, 1989;Rettie & Messier, 2000;Johnson et al, 2004;Gustine et al, 2006;Mayor et al, 2007). Terrain, snow conditions, habitat characteristics and predation pressure are all interrelated to some degree.…”
Section: Introductionmentioning
confidence: 99%
“…Looking across the northern landscape, caribou ecotype and disturbance (e.g., wildfire and/or industrial development) are also likely to be important factors in determining distribution (Mallory & Hillis, 1998;Johnson et al, 2005;Joly et al, 2007a). The importance of each factor is likely to depend on the scale of the analysis (Wiens, 1989;Rettie & Messier, 2000;Johnson et al, 2004;Gustine et al, 2006;Mayor et al, 2007). Terrain, snow conditions, habitat characteristics and predation pressure are all interrelated to some degree.…”
Section: Introductionmentioning
confidence: 99%
“…The most parsimonious landscape-level model included slope and elevation, whereas the patch-scale model contained vegetation cover types extracted from GIS. Unlike Apps et al (2001), Johnson et al (2004) found that stand age was not a predictive variable in their patch-scale analysis. The authors note that the homogenous distribution of old forest in their study area precluded the opportunity for selection, but they expected that if the area was subject to logging or wildfire, age would likely become predictive at this scale (Johnson et al, 2004).…”
Section: Intermediate Scales: Habitat Selection Within Subpopulationsmentioning
confidence: 85%
“…Unlike Apps et al (2001), Johnson et al (2004) found that stand age was not a predictive variable in their patch-scale analysis. The authors note that the homogenous distribution of old forest in their study area precluded the opportunity for selection, but they expected that if the area was subject to logging or wildfire, age would likely become predictive at this scale (Johnson et al, 2004). Ultimately, the patch and landscape maps were combined to provide a map that was used in conjunction with other information by land-use planners and caribou recovery groups (RIP, 2005).…”
Section: Intermediate Scales: Habitat Selection Within Subpopulationsmentioning
confidence: 85%
See 2 more Smart Citations